Bortezomib and other proteosome inhibitors—induced peripheral neurotoxicity: From pathogenesis to treatment. (24th October 2019) - Velasco, Roser; Alberti, Paola; Bruna, Jordi; Psimaras, Dimitri; Argyriou, Andreas A.
Abstract: Proteasome inhibitors (PIs), especially bortezomib (BTZ), have come to the forefront over the last years because of their unprecedented efficacy mainly against multiple myeloma (MM). Unfortunately, peripheral neuropathy (PN) secondary to treatment of MM with PIs has emerged as a clinically relevant complication, which negatively impacts the quality of life of MM survivors. Bortezomib‐induced peripheral neuropathy (BIPN) is a dose‐limiting toxicity, which develops in 30% to 60% of patients during treatment. Typically, BIPN is a length‐dependent sensory axonopathy characterized by numbness, tingling, and severe neuropathic pain in stocking and glove distribution. BIPN mechanisms have not yet been fully elucidated. Experimental studies suggest that aggresome formation, endoplasmic reticulum stress, myotoxicity, microtubule stabilization, inflammatory response, and DNA damage could contribute to this neurotoxicity. A new generation of structurally distinct PIs has been developed, being increasingly used in clinical settings. Carfilzomib exhibits a much lower neurotoxicity profile, with a significantly lower incidence of PN compared to BTZ. Pre‐existing PN increases the risk of developing BIPN. Besides, BIPN is related to dose, schedule and mode of administration and modifications of these factors have lowered the incidence of PN. However, to date there is no cure for PIs‐induced PN (PIIPN), and a careful neurological monitoring and dose adjustment is a key strategy for preserving quality of life. This review critically looks at the pathogenesis, incidence, risk factors, both clinical and pharmacogenetics, clinical phenotype and management of PIIPN. We also make recommendations for further elucidating the whole clinical spectrum of PIIPN.